(untitled) (Confluenţe Bibliologice, 2014)
Gurie Grosu was elevated to the rank of Archbishop of Chisinau and Khotin on March 29, 1921. He was appointed Archbishop of this diocese by Royal Decree No. 5481/921. The ceremony of elevation took place in Bucharest, in the Royal Palace, in the presence of the King and the Royal Family. Hieromonk Gurie Grosu always feared foreign domination, wandered from village to village under the wing of the Church to spread the spiritual word in the native language of the Church, singing with the people and distributing to them a small book, which was the first alphabet in the Romanian language in Bessarabia.